Implementasi Nilai-nilai Amanah pada Karyawan Hotel Darussalam Pondok Pesantren Gontor di Ponorogo - Sri Herianingrum; Meri Indri Hapsari; Syahruddin Syahruddin (Al Tijarah, 2015)
This research aims to know the assessment of the implementation of the amanah in employees Darussalam Hotel at Pondok Pesantren Gontor Ponorogo. This research focuses on the discussion of the amanah. Amanah could mean everything to fulfi ll deposited and entrusted to a person. This study used a qualitative approach to exploratory case study strategy. File was collected through interviews to employees Darussalam Hotel at Pondok Pesantren Gontor Ponorogo. The results of this study show that the majority of informants has been carrying out the nature of the amanah to implement their duties as employee of Darussalam Hotel at Pondok Pesantren Gontor Ponorogo, it can be seen by the attitude of the employees who are able to demonstrate a sense of responsibility, just promise with high work commitment and transparency in carrying out its duties. The nature of the mandate carried out in the service process in carrying out each task by the employee for the service that the mandate would have a positive impact for the hotel as one of the Pondok Gontor’s Business.